Identifying Research Frontiers In Dynamic Pricing Capability And Revenue Optimization Using Bibliometric Science Mapping Techniques - La Ode Sugianto; Dwi Warni Wahyuningsih; Siti Chamidah; Wa Ode Sitti Nurrhamah; La Harjono (JURNAL ECONOMINA, 2026)
This study aims to identify the knowledge structure, patterns of scientific collaboration, the evolution of research themes, and research frontiers in the study of Dynamic Pricing Capability (DPC) and Revenue Optimization (RO) during the period 2020-2025. The study uses a quantitative-descriptive bibliometric approach with data sources derived from the Dimensions database using the keywords "Dynamic Pricing Capability and Revenue Optimization". The analysis was conducted using VOSviewer software through seven main visualizations: annual publication trends, network visualization, overlay visualization, density visualization, author collaboration, institutional collaboration, and country collaboration. The results show that publications in this field experienced very significant growth, especially in the period 2024-2025, indicating increasing academic attention to dynamic pricing strategies in the era of digital transformation. The themes of price and profitability optimization, supply and demand chain management, organizational capabilities and innovation, and data-driven digital transformation dominate the research knowledge structure. Collaboration analysis shows the dominance of contributions from China, the United States, and a number of leading research institutions that form a global scientific network. Meanwhile, the analysis of the theme's evolution reveals a shift in research focus from an operational approach to the integration of artificial intelligence, machine learning, the digital economy, and organizational innovation. These findings indicate that DPC has evolved into a strategic capability that supports competitive advantage and optimizes organizational revenue. This research contributes to mapping the development of knowledge and identifying future research directions in the areas of Dynamic Pricing Capability and Revenue Optimization.